Conceptualizing Information Literacy for National Development - Kaku, David (My University, 2023)
The concept of information literacy is a subject of serious debate among scholars in the information profession. The controversy surrounding the subject may well be due to proliferation in the information and communication technology (ICT) and the diversity of the world’s culture. In this paper: Conceptualizing Information Literacy for National Development, the study looked at the relationship between the concept of information literacy and national development, the definition of the concept as attempted by different authors. The study also x-rayed the socio-cultural construct (Theory) of the concept and American Association of School Librarians (AASL) theory. They identified individual elements of information literacy consistent the two theories which include: Recognition of information needs; location and evaluation of the quality of information; store and retrieve information; make effective and ethical use of information, and apply information to create and communicate knowledge. They concluded that, any country that strives for sustainable national development must of necessity strives towards ensuring that, its citizens achieve the status of information literacy in the context peculiar to such environment.
Keywords: Information; Literacy and National Development